The Effect of Financial Literacy and Investment Behavior on Financial Inclusion through Financial Behavior as a Mediating Variable in the Sandwich Generation - Dea Permatasari; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
This study looks at how investment behavior and financial literacy affect financial inclusion within Indonesia's sandwich generation. A structural equation model with SmartPLS was used to examine the quantitative data acquired from 105 respondents via online purposive sampling. The results demonstrate that financial conduct has considerable financial behavior that is significantly impacted by financial inclusion and financial knowledge. However, financial literacy has no direct bearing on financial inclusion or investment behavior, and financial conduct is not significantly influenced by investment activity.